THE TRANSVAAL REBELLION: THE FIRST BOER WAR 1880-1881/JOHN LABAND - Van der Waag, Ian (Scientia Militaria - South African Journal of Military Studies, 2011)
Defying their British rulers, the Boers of the Transvaal rose in rebellion in December 1880. A British column, moving between Bronkhorstspruit and Pretoria, was attacked by a Boer commando and almost annihilated and the seven British garrisons in the territory were invested by bands of Boers, ignited by a burgeoning Afrikaner nationalism and a desire for independence. The events caused a flurry in distant Britain, where the government, inundated with domestic concerns and wary of further stimulating Afrikaner nationalism, decided to grant self-rule to the Transvaal. Yet, in the meantime, events in South Africa moved apace. The relief column, commanded by Major General Sir George Pomeroy Colley, was defeated three times within almost as many weeks and the garrisons lost all hope of reinforcement. The political settlement, patched eagerly together by a London focussed on pressing domestic troubles, was condemned by Greater Britons in Britain and South Africa.